The Threat of Judicial Mafia in Indonesia in Discrediting the Principle of the Rule of Law - Zoelva, Hamdan (International Journal of Criminology and Sociology, 2021)
This paper aims to critically analyze law enforcement against the mafia of the court. The purpose is to improve the quality of legal institutions and improve the legal structure dimension. The objective is to obtain the quality of court institution as closely related to the apparatus's quality and integrity and the integrity of the apparatus to be ensured since the recruitment process also maintains the coaching process. Using the socio-legal approach, the analysis was directed to the practice of mafia threats to the principle of independence and the court's impartiality while threatening the existence of the rule of law. The results showed that the mafia of court arises because of the collusion among the elements of the court's stakeholders, the destruction of the stakeholders that led to the emergence of the various mafia of court practices in Indonesia. The main findings of this study are that the court, as the last bastion of justice and law enforcement, is undoubtedly expected to be independent and impartial following the demands of the rule of law. As a practical implication, the court institution cannot be independent and impartial if there is still a network of crimes that undermine the court system. Courts that only give justice to those who are strong and have access will cultivate what is feared by some legal experts that law is only a tool as instrumentalism for those who have access and power. This is where the threat to the principle of the rule of law lies.